Law, War And Peace: are the Laws Silent During the War? - Stovba, Oleksii (Archives of Criminology and Forensic Sciences, 2022)
The research paper is devoted to understanding the way of existence of law during the war. This is done by referring to theoretical and methodological foundations of philosophical thought: legal positivism, ideas of natural law and the sociological school of law. At the same time, these approaches are considered on the basis of the latest philosophical and legal studies. Based on the views of E. Bulygin, R. Alexy and other outstanding representatives of modern legal thought, the author examines the classical ways of the existence of law: normative legal act, the idea of law, custom, and comes to the conclusion that law can’t exist in the named modes. Therefore, there is an objective need to rethink the mentioned problem in the coordinates of non-classical philosophy of law, first of all, legal phenomenology. One of the most successful phenomenological strategies is phenomenological reduction. The essence of such operation is to reduce all random empirical properties of the object in order to reveal its essence. In contrast to the traditional conceptual analysis, the reduction of the classical forms of the existence of law results in a “remainder” of law in the form of a person’s bodily existence, which sets a limit to the actions of other people. This limit is specified with the help of three factors: locality, modality and subjectivity. Locality means that the corporeality of a person under conditions of war embodies the rule of law not anywhere, but only in a certain territory. In turn, modality as a factor in the existence of law during the war indicates that human corporeality as a mode of existence of law can be violated only in certain ways. The third of the mentioned features, subjectivity, means that corporeality is the embodiment of the norm of the law only in relation to certain subjects (e.g., non-combatants). Thus, human corporeality becomes a living embodiment of law and in this capacity replaces the classical norm contained in a normative legal act or precedent, a subjective or objective idea of law, as well as legal custom as a traditionally formed template of social relations. Therefore, it should be concluded that under the conditions of war, the law can exist only in the form of the living bodily presence of a person, and the experience of law from the sphere of ideas and norms moves to the plane of corporeality, when the offense is initially interpreted not as a violation of a natural or positive norm, but as causing bodily harm to a person. This, in turn, allows us to create a more realistic picture of functioning of the law during military operations, when instead of a static and uniform legal field that is constantly violated, we are dealing with a heterogeneous